CAUSES OF EMPTINESS DRUGS AND MEDICAL DEVICES CONSUMABLES AT THE REGIONAL PUBLIC HOSPITAL PHARMACEUTICAL WAREHOUSE - Burhan, M.; Harijanto, Tatong; Roosalina, Arma (Jurnal Aplikasi Manajemen, 2018)
One of the main indicators of quality of hospitals Bangil is the incidence of emptiness drugs and medical devices consumables in the pharmaceutical warehouse. In January to August 2016, the incidence rate is still high vacancy. The high incidence of these gaps affects the quality of hospital services. This study aims to determine the factors that cause a high incidence of emptiness drugs and medical devices consumables in the pharmaceutical warehouseRegional public hospital at bangil. Factors that cause the problems can be found using the fishbone analysis method. The research is qualitative research with the informant as follows: head of the pharmacy, head of the outpatient pharmacy, head of the inpatient pharmacy, pharmaceutical warehouse chief, commitment maker official, technical implementation official. The data obtained from depth interviews with the informant. Identification of alternative solutions was conducted using Focus Group Discussion (FGD). Factors that were discovered and became a priority issue is no calculation of the minimum stock and maximum stock at the pharmacy module hospital information system (SIMRS). Alternative solutions isto create a policy on the calculation of minimum stock and maximum stock of drugs and medical devices consumable in hospital pharmacy.